2014
DOI: 10.1016/j.eplepsyres.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D levels are common in patients with epilepsy

Abstract: SUMMARY Purpose Vitamin D is important for bone health, and vitamin D deficiency may contribute to other disorders (e.g., autoimmune, infections, cancer, degenerative, diabetic, and vascular). Enzyme-inducing antiepileptic drugs have been particularly implicated for osteoporosis risk given their effects on vitamin D. We examined the prevalence of vitamin D deficiency in adult epilepsy patients. Methods We conducted an observational study of consecutive epilepsy patients treated by two clinicians at the Emor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 29 publications
1
41
2
10
Order By: Relevance
“…First, subjects with SMID have various health problems including nutritional ones. However, reports on the vitamin status in subjects with SMID have been quite limited, except for the effect of anti-epileptic drugs, which are commonly administered to people with SMID, on the catabolism of vitamin D and folate deficiency (13,14). Studies on water-soluble vitamins including vitamin B12 have been scarce.…”
Section: Discussionmentioning
confidence: 99%
“…First, subjects with SMID have various health problems including nutritional ones. However, reports on the vitamin status in subjects with SMID have been quite limited, except for the effect of anti-epileptic drugs, which are commonly administered to people with SMID, on the catabolism of vitamin D and folate deficiency (13,14). Studies on water-soluble vitamins including vitamin B12 have been scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Borusiak et al [43] uniquely suggested the downregulation of vitamin D not only occur in epileptic but also in otherwise healthy children receiving AEDs. Some reports also proposed that vitamin D deficiency was significantly frequent in patients taking EIAEDs but still common in those taking non-EIAEDs [44][45][46][47] . On the other hand, VPA, a wide-spectrum AED, is commonly regarded as an inhibitor of cytochrome P450 system, but this belief was recently challenged, as VPA was reported to augment the expressions of CYP24 and CYP3A4 through in vitro experiments [48,49] .…”
Section: Discussionmentioning
confidence: 99%
“…Among the conventional AEDs, early reports have focused on inducers of cytochrome P450 (CYP) enzyme such as carbamazepine, phenobarbital, phenytoin and primidone that can activate the PXR, increasing vitamin D metabolism and eventually leading to hypocalcemia and secondary hyperparathyroidism (113). In a total of 600 patients receiving AEDs, 45% had 25(OH)D level <20 ng/mL while deficiency was present in 54% of enzyme-inducing and 37% of non-enzyme-inducing antiepileptic drug groups (114). Interestingly, Tombini et al found that patients taking multiple AEDs had lower levels of 25(OH)D than patients taking single therapy, with 25(OH)D levels depending on treatment duration (115).…”
Section: Antiepileptic Drugsmentioning
confidence: 99%